COORDINATES CALCULATION OF DETECTED AND RECOGNIZED OBJECTS IN SURVEILLANCE SYSTEMS - Simonyan, D.A. (Proceedings of the YSU A: Physical and Mathematical Sciences, 2018)
The detection and recognition of objects in images has found a wide application in many spheres. It is used in the surveillance system, cartography, robotics, medicine, etc. In many surveillance systems the localization of the detected object has a great significance. After localizing the object, it will be possible to carry out the calculation of its coordinates. The formulas for calculating the object-camera distance are rather theoretical. Conducting experiments and verifying formulas in practice would have a high significance, as the distance of the object from camera is an essential precondition for object’s coordinate calculation.